SITOTOKSISITAS DAN EFEK PROTEKSI TURUNAN SENYAWA SINAMOIL KALIKS (4) RESORSINARENA TERHADAP VIABILITAS SEL FIBROBLAS KULIT NORMAL MANUSIA YANG TERPAJAN SINAR ULTRA VIOLET B (UVB) - , Yuni Eka Anggraini ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human skin exposed to ultraviolet B (UVB), as an essential component of sunlight, associated with severe oxidative stress on the skin. The use of photoprotection is needed to prevent the harmful effects of UVB rays. Cinnamoyl calix[4]resorcinarene is a conjugate between cinnamoyl chloride as cinnamic acid group with calix[4]resorsinarene. Both are aromatic compounds that can absorb UV light, especially calix[4]resorsinarena which is rich of electron conjugation as a UV trap. Besides being able to absorb UV ray, cinnamic acid group are also potentially toxic to cells, meanwhile according to previous studies, calix[4]resorsinarene and its derivatives were no cytotoxic and stable in nature. Derivatives of cinnamoyl calix[4]resorcinarene tested were cinnamoyl Cmetilcalix[ 4]resorcinarene (substance 1), cinnamoyl C-fenilcalix[4]resorcinarene (substance 2), and C-phenyl calix[4]octaresorcinnaryl cinnamate (substance 3). This study aims to determine the cytotoxicity and protective effect of those group of Cinnamoyl calix[4]resorcinarene derivatives on viability of normal human skin fibroblasts exposed to UVB. For toxicity tests, cultures of normal skin fibroblasts were mixed with solutions of three tested compunds in the various concentrations of 0.04%, 0.08%, 0.16%, and 0.32%. After incubation for 24 h, viability was assessed by MTTassay. To test the protective effect, those compunds creams in the various concentrations of 0.16%, 0.32%, 0.64%, and 1.28% swere meared on the lid of 96-well plates of fibroblast cells, then well plates were exposed with 100 mJ/cm2 UVB ray. After incubation for 24 h, viability was assessed by MTT-assay. The mean differences of optical density (OD) were analyzed with Friedman and Wilcoxon (p <0.05) The results obtained for toxicity tests were substance 1 not toxic up to the concentration of 0.32% (p = 0.671), substance 2 up to 0.08% (p = 0.551), whereas substance 3 not toxic in all concentrations. In the protective effect test, there were no significance differences of fibroblast viability between all tested substances and base+UV control (p> 0.05), although at a concentration of 1.28%, test substance 1 and 3 had a higher viability than base+UV control. In conclusion, the toxicity of the sinamoyl C-metilcali[4]resorcinarene and Cphenylcalix[ 4]rescorcinaryl octa cinnamate increased as the concentrations gradualy raised up and all tested substances had no statistically significant protective effect on fibroblast viability.